Effectiveness of Fenbendazole and Metronidazole Against Giardia Infection in Dogs Monitored for 50-Days in Home-Conditions - Ciuca, Lavinia; Pepe, Paola; Bosco, Antonio; Caccio, Simone Mario; Maurelli, Maria Paola; Sannella, Anna Rosa; Vismarra, Alice; Cringoli, Giuseppe; Kramer, Laura; Rinaldi, Laura; Genchi, Marco (Frontiers in Veterinary Science, 2021)
A field trial performed in-home conditions was conducted on 24 dogs naturally infected with Giardia, in order to compare the efficacy of fenbendazole and metronidazole. Animals were allocated in groups randomly in order to obtain two groups of 12 dogs each with similar parasitic loads of Giardia cysts: dogs in Group A were treated with fenbendazole (Panacur®, Intervet Italia Srl) administered at the dose of 50 mg/kg orally once a day for five consecutive days, dogs in Group B were treated with metronidazole (Flagyl®, Zambon Italia Srl) administered orally at the dose of 50 mg/kg, once a day for five consecutive days. All the dogs that were shedding Giardia cysts after the first treatment (Day 0) were retreated (either at Day 7 or at Day 14 or at Day 21) until a negative result was obtained with the same treatment. Additionally, all the dogs were re-examined at Day 50. All the dogs were tested for the presence of Giardia cysts using a faecal flotation method (FLOTAC). The percent efficacy of the treatments (A and B) was calculated at each sampling point (Days 7, 14, 21, 50) as reduction in mean Giardia cysts. After the first therapy, on day 7, 4/12 (33.3%) dogs tested positive for Giardia cysts in the Group A and 5/12 (41.7%) in the Group B. Efficacies at (Days 7, 14, 21, 50) of the treatments against Giardia infection were 80.9%, 94%, 100% and 97% in the Group A and 70.8%, 99%, 100% and 97.1% in the Group B. Statistically significant differences were not observed between the efficacy of Fenbendazole and Metronidazole against infection by G. duodenalis (P=0.686). Molecular analysis revealed full homology (i.e., 100% with JN416550) with the canine specific assemblage D in six positive dogs. Different hypotheses might explain the re-appearance of the Giardia cysts in some dogs after treatment, e.g. re-infection from the home environment, the correct medication given by the owners, the diet, as well as treatment failure, but also biological issues related to the intermittent excretion of Giardia cysts.